The Importance of English in International Science Research Collaboration - Kawakibi, M. Akhsanal; Indrawan, Fani (Teaching English as Foreign Language, Literature and Linguisticss, 2024)
In international science research, English has emerged as the dominant lingua franca, facilitating communication and collaboration across diverse linguistic and cultural backgrounds. This study explores the role of English in global scientific forum, particularly in research collaboration, publication, and international forums. English enables faster communication and comprehension among researchers, thus enhancing the efficiency and effectiveness of collaborative efforts. Using a structured methodology, this study identifies the most frequently used English terminologies in scientific publications and underscores their significance in conveying complex scientific ideas. The findings reveal some vocabularies are heavily used in scientific publications which gives an insight for English learners especially for academic setting who may need to publish their writing into international publications. This paper concludes that mastering English is essential for researchers aiming to engage in international collaborations and contribute to the advancement of global science.